Leaching of copper slags in sulphuric acid and alkaline glycine media - Mura, Mauricio; Castillo, Ignacio; Hernández, Pía C.; Galleguillos Madrid, Felipe M.; Salinas-Rodríguez, Eleazar; Castillo, Jonathan; Soliz, Álvaro; Gálvez, Edelmira; Toro, Norman (Frontiers in Chemical Engineering, 2025)
Copper slag is industrial waste, having fayalite and magnetite as main phases, copper is present in the form of chalcopyrite and chalcosine. However, the complex structure of the slag makes the dissolution process difficult, which is why methods have been used to recover metals with leaching in sulfuric acid media as a traditional technique. however, the use of new leaching agents has been implemented, for instance, glycine. The operating parameters such as concentration, temperature, particle size are compared in these leaching media, highlighting glycine with high selectivity and efficiency unlike sulfuric acid in alkaline conditions to leach copper. In this study, the efficiency of glycine as a leaching agent for copper recovery will be revised.